Molybdenum / tin selenide / sulfur-nitrogen co-doped graphene composite material, preparation method thereof and lithium ion energy storage device
By using the negative electrode material of molybdenum/tin selenide/sulfur nitrogen co-doped graphene composite in lithium-ion energy storage devices, the problem of insufficient electrochemical performance of lithium-ion capacitors is solved, and higher energy density and power density are achieved, which is suitable for large-scale production.
Patent Information
- Application Number
- CN202411335373.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-09-24
AI Technical Summary
The electrochemical performance of existing lithium-ion capacitors has not yet reached room for improvement, especially in terms of energy density and power density.
MoSe2-SnSe composite nanoparticles are used as the negative electrode material for lithium-ion energy storage devices, and MoSe2-SnSe composite nanoparticles are grown in situ on both sides of the two-dimensional sulfur-nitrogen co-doped graphene (SNG) sheet structure to form a three-dimensional porous composite structure with stable structure.
It improves the electrochemical performance of lithium-ion batteries and lithium-ion capacitors, enhances conductivity, alleviates the volume expansion effect during charging and discharging, improves the theoretical specific capacity and lithium storage active sites, and is suitable for large-scale production.
Smart Images

Figure CN119864388A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of electrochemical energy storage, and in particular relates to a molybdenum / tin selenide / sulfur-nitrogen co-doped graphene composite material and a preparation method thereof, and a lithium ion energy storage device. Background Art
[0002] In recent years, with the construction of new energy systems, higher requirements have been put forward for energy storage devices. In particular, the rapid development of electric vehicles and the widespread application of mobile digital electronic devices require a safe, low-cost energy storage element with both high energy density and long cycle stability. Among the many energy conversion and storage devices, lithium-ion batteries and supercapacitors have become research hotspots. The two have similar compositions, but the different energy storage mechanisms lead to obvious differences in various performances. For lithium-ion batteries, charge storage is mainly based on lithium insertion, alloying reactions or conversion reactions on the surface and bulk of the material, so it has the characteristics of high specific capacity. Supercapacitors rely on double-layer or pseudocapacitive conversion reactions to store charge, and have the characteristics of high power density and long cycle life. Therefore, it is particularly important to combine the internal components of the device to develop a new energy storage device with both high energy density and high power density, which has led to the birth of lithium-ion capacitors.
[0003] As a new type of asymmetric capacitor, lithium-ion capacitors combine the negative electrode materials of lithium-ion batteries and the positive electrode materials of supercapacitors in electrode materials, so they have the electrochemical characteristics of both devices. During the charging process, the lithium ions in the electrolyte are embedded in the negative electrode to form lithium-intercalated compounds, while the anions in the electrolyte are adsorbed on the surface of the positive electrode activated carbon to form an electrical double layer; the discharge process is the opposite of the charging process, the lithium ions are released from the lithium-intercalated materials, and the anions are also desorbed from the activated carbon surface back to the electrolyte. This design greatly increases the energy density of lithium-ion capacitors, reduces weight, and broadens the voltage range. Moreover, the design of graphite + activated carbon also makes lithium-ion capacitors easier to recycle. Practice has proved that some lithium-ion capacitors have been commercialized. However, compared with lithium-ion batteries, the electrochemical performance of lithium-ion capacitors still has a lot of room for improvement. Summary of the invention
[0004] In order to solve the problems existing in the prior art, the purpose of the present invention is to provide a molybdenum / tin selenide / sulfur-nitrogen co-doped graphene composite material and a preparation method thereof and a lithium ion energy storage device. The composite material of the present invention has the characteristics of lower cost, high electrochemical performance and stable structure.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows: A method for preparing a molybdenum / tin selenide / sulfur-nitrogen co-doped graphene composite material comprises the following steps: Sodium molybdate tetrahydrate, sodium stannate trihydrate, thiourea and dicyandiamide are mixed with graphene oxide dispersion to obtain suspension A; wherein the mass ratio of sodium molybdate tetrahydrate, sodium stannate trihydrate, thiourea and dicyandiamide is 1:(0.8-2):(0.8-1.8):(1-3), and the mass ratio of sodium molybdate tetrahydrate to graphene oxide is (1.5-3):1; The suspension A is subjected to a hydrothermal reaction at 160-190° C. After the reaction is completed, the product is cooled, centrifuged, washed, and freeze-dried to obtain a precursor material; The precursor material is placed in a reducing atmosphere and calcined at 500-600° C. After the calcination, the molybdenum / tin selenide / sulfur-nitrogen co-doped graphene composite material is obtained.
[0006] Preferably, the dispersant of the graphene oxide dispersion is a mixed solvent of water and ethanol, wherein the mixed solvent of water and ethanol is obtained by mixing water and ethanol in a volume ratio of (1-3):1; In the graphene oxide dispersion, the solid-liquid ratio of graphene oxide to dispersant is (40-60):40, and the unit is mg / mL.
[0007] Preferably, the suspension A is subjected to hydrothermal reaction at 160-190° C. for 18-22 hours.
[0008] Preferably, after the hydrothermal reaction of suspension A is completed, the product is cooled to room temperature and then centrifuged, washed, and freeze-dried.
[0009] Preferably, the reducing atmosphere during calcination of the precursor material is a mixed gas of hydrogen and argon.
[0010] Preferably, the volume fraction of hydrogen in the mixed gas of hydrogen and argon is 5% to 10%; when the precursor material is calcined, the flow rate of the mixed gas of hydrogen and argon is 30 to 70 SCCM.
[0011] Preferably, when the precursor material is calcined, the heating rate is 3 to 5° C. / min and the calcination time is 2 to 3 hours.
[0012] The present invention also provides a molybdenum / tin selenide / sulfur-nitrogen co-doped graphene composite material prepared by the above preparation method of the present invention.
[0013] The present invention also provides a lithium ion energy storage device, comprising a positive electrode and a negative electrode, wherein the material of the negative electrode is the molybdenum / tin selenide / sulfur-nitrogen co-doped graphene composite material of the present invention as described above.
[0014] Preferably, the lithium ion energy storage device is a lithium ion battery and a lithium ion hybrid capacitor.
[0015] Compared with the prior art, the present invention has the following beneficial effects: In the molybdenum / tin selenide / sulfur-nitrogen co-doped graphene (MoSe2-SnSe@SNG) composite material provided by the present invention, MoSe2-SnSe composite nanoparticles containing heterogeneous structures are in-situ grown on both sides of the two-dimensional SNG sheet structure to form a three-dimensional porous composite structure with stable structure. In the MoSe2-SnSe@SNG composite structure, MoSe2-SnSe nanoparticles can inhibit the stacking of SNG, and SNG can also effectively inhibit the particle agglomeration and volume expansion of MoSe2-SnSe nanoparticles during the charging and discharging process, and can also effectively improve the electronic conductivity of MoSe2-SnSe as a three-dimensional conductor; MoSe2-SnSe composite material has a high theoretical specific capacity as a conversion-alloy type negative electrode, and at the same time, the heterogeneous interface of MoSe2 and SnSe can provide more lithium storage active sites, and the two can cooperate with each other to effectively improve the electrochemical performance of lithium ion batteries and lithium ion capacitors. Therefore, the MoSe2-SnSe@SNG composite material disclosed by the present invention is a relatively ideal lithium storage negative electrode material. The preparation method of the MoSe2-SnSe@SNG composite material provided by the present invention is simple, adjustable and controllable, the cost of the required raw materials is low, and the preparation process is relatively simple, so that the product has higher purity and is more suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. The embodiments of the present invention are described in detail below in conjunction with the accompanying drawings, wherein: Figure 1 This is the X-ray powder diffraction spectrum of the MoSe2-SnSe@SNG composite material prepared in Example 3 of the present invention.
[0017] Figure 2 This is a SEM image of the MoSe2-SnSe@SNG composite material prepared in Example 3 of the present invention. Figure 3 This is a TEM image of the MoSe2-SnSe@SNG composite material prepared in Example 3 of the present invention.
[0018] Figure 4 This is a SEM image of the MoSe2@SNG composite material prepared in Example 3 of the present invention. Figure 5 This is a SEM image of the SnSe@SNG composite material prepared in Example 3 of the present invention. Figure 6This is a lithium storage cycle performance diagram of SnSe@SNG, MoSe2@SNG, MoSe2-SnSe@SNG and SNG composite materials prepared in Example 3 of the present invention at 0.2 A / g.
[0019] Figure 7 This is a lithium storage rate performance diagram of a lithium ion hybrid capacitor assembled with MoSe2-SnSe@SNG and activated carbon AC prepared in Example 3 of the present invention.
[0020] Figure 8 This is the rate performance diagram of the MoSe2-SnSe@SNG||AC lithium-ion hybrid capacitor assembled in Example 3. DETAILED DESCRIPTION
[0021] The specific implementation of the embodiment of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.
[0022] The preparation method of the molybdenum / tin selenide / sulfur-nitrogen co-doped graphene composite material of the present invention comprises the following steps: (1) Sodium molybdate tetrahydrate, sodium stannate trihydrate, thiourea and dicyandiamide are added to a dispersion of graphene oxide, and the mixture is stirred at room temperature for 1 hour to obtain a suspension A; the suspension A is transferred into an autoclave for a hydrothermal reaction at a temperature of 160-190°C and a reaction time of 18-22 hours; after sufficient reaction, the reaction product is cooled, centrifuged, washed and freeze-dried to obtain a precursor material; wherein the mass ratio of sodium molybdate tetrahydrate, sodium stannate trihydrate, thiourea and dicyandiamide is 1:(0.8-2):(0.8-1.8):(1-3), and the mass ratio of sodium molybdate tetrahydrate to graphene oxide is (3-1.5):1; in the dispersion of graphene oxide, the solvent is a mixed solvent prepared by mixing water and ethanol in a volume ratio of (1-3):1.
[0023] (2) The above-mentioned polymer precursor product and selenium powder are placed in a reducing atmosphere, calcined at 500-600°C for 2-3 hours, the heating rate is 3-5°C / min, and the flow rate of the protective gas is 30-70SCCM to obtain a MoSe2-SnSe@SNG composite material (i.e., MoSe2-SnSe nanoparticles supported on sulfur-nitrogen co-doped graphene composite material). The above-mentioned reducing atmosphere uses a mixed gas of argon and hydrogen Ar / H2 (wherein the volume ratio of Ar to H2 in Ar / H2 is 95% / 5% or 90% / 10%).
[0024] The MoSe2-SnSe@SNG composite material of the present invention can be applied to lithium-ion energy storage devices (such as lithium-ion batteries and lithium-ion hybrid capacitors). The MoSe2-SnSe@SNG composite material of the present invention can effectively improve the conductivity of the electrode material and alleviate the volume expansion effect of the electrode material during the charging and discharging process, thereby achieving the purpose of improving the electrochemical performance of lithium-ion batteries and lithium-ion capacitors.
[0025] Example 1 The preparation method of the MoSe2-SnSe@SNG composite material in this embodiment includes the following steps: 1. First, 40 mg of graphene oxide was dispersed in 40 mL of distilled water / ethanol mixed solvent (water: ethanol volume ratio is 1:1) to obtain a graphene suspension; then 60 mg of sodium molybdate tetrahydrate, 48 mg of sodium stannate trihydrate, 48 mg of thiourea, and 60 mg of dicyandiamide were added to the above graphene suspension, and stirred at room temperature for 1 hour. After stirring evenly, suspension A was obtained; suspension A was transferred to an autoclave for hydrothermal reaction at a temperature of 160 ° C for 22 hours; after sufficient reaction, the reaction product was cooled, centrifuged, washed, and freeze-dried to obtain a precursor material; 2. The above-mentioned polymer precursor product and selenium powder were placed in a reducing atmosphere (Ar and H2 volume ratio of 90% / 10%) with a gas flow rate of 30 SCCM, and the temperature was increased to 500 °C at 5 °C / min and maintained for 3 hours to obtain a MoSe2-SnSe@SNG composite material.
[0026] Comparative Example 1 The steps are basically the same as those in the above-mentioned embodiment 1, except that in step 1, no sodium molybdate tetrahydrate or sodium stannate trihydrate is added, and the SnSe@SNG or MoSe2@SNG composite material can be obtained.
[0027] Example 2 The preparation method of the MoSe2-SnSe@SNG composite material in this embodiment includes the following steps: 1. First, 50 mg of graphene oxide was dispersed in 40 mL of distilled water / ethanol mixed solvent (water: ethanol volume ratio is 2:1) to obtain a graphene suspension; then 100 mg of sodium molybdate tetrahydrate, 100 mg of sodium stannate trihydrate, 180 mg of thiourea, and 300 mg of dicyandiamide were added to the above graphene suspension, and stirred at room temperature for 1 hour. After stirring evenly, suspension A was obtained; suspension A was transferred to an autoclave for hydrothermal reaction at a temperature of 180 ° C for 20 hours; after sufficient reaction, the reaction product was cooled, centrifuged, washed, and freeze-dried to obtain a precursor material; 2. The above-mentioned polymer precursor product and selenium powder were placed in a reducing atmosphere (Ar and H2 volume ratio of 90% / 10%) with a gas flow rate of 50 CCM, and the temperature was increased to 550 °C at 3 °C / min and maintained for 2 hours to obtain a MoSe2-SnSe@SNG composite material.
[0028] Comparative Example 2 The steps are basically the same as those in the above-mentioned embodiment 2, except that in step 1, no sodium molybdate tetrahydrate or sodium stannate trihydrate is added, and the SnSe@SNG or MoSe2@SNG composite material can be obtained.
[0029] Example 3 The preparation method of the MoSe2-SnSe@SNG composite material in this embodiment includes the following steps: 1. First, 60 mg of graphene oxide was dispersed in 40 mL of a distilled water / ethanol mixed solvent (the volume ratio of water to ethanol was 2:1) to obtain a graphene suspension; then 180 mg of sodium molybdate tetrahydrate, 360 mg of sodium stannate trihydrate, 540 mg of thiourea, and 540 mg of dicyandiamide were added to the graphene suspension, and stirred at room temperature for 1 hour. After stirring evenly, suspension A was obtained; suspension A was transferred into an autoclave for hydrothermal reaction at a temperature of 190°C for 22 hours; after sufficient reaction, the reaction product was cooled, centrifuged, washed, and freeze-dried to obtain a precursor material; 2. The above-mentioned polymer precursor product and selenium powder were placed in a reducing atmosphere (Ar and H2 volume ratio of 95% / 5%), the gas flow rate was 60 CCM, the temperature was increased to 600 °C at 3 °C / min and maintained for 2 hours to obtain MoSe2-SnSe@SNG composite material.
[0030] Comparative Example 3 The steps are basically the same as those in the above-mentioned embodiment 3, except that in step 1, no sodium molybdate tetrahydrate or sodium stannate trihydrate is added, and the SnSe@SNG or MoSe2@SNG composite material can be obtained.
[0031] The structure and morphology of the obtained samples were characterized by X-ray diffractometer, scanning electron microscope (SEM) and transmission electron microscope (TEM). Figure 1 , Figure 2 , Figure 3 .Depend on Figure 1 It can be seen that the XRD spectra of MoSe2-SnSe@SNG, MoSe2@SNG and SnSe@SNG composite samples all correspond to the standard cards of MoSe2 and SnSe, proving that the MoSe2-SnSe@SNG composite material was successfully prepared. Figure 2 ) and TEM ( Figure 3 ) figure, it can be seen that MoSe2-SnSe nanosheets can be uniformly loaded on the SNG substrate to form a three-dimensional multi-level composite material, and the two-dimensional thin film material, namely the SNG substrate, can be clearly observed in the TEM image. In contrast, the two-dimensional MoSe2 nanosheets cannot be clearly observed in the SEM image of MoSe2@SNG ( Figure 4 ), which is mainly attributed to the uniform dispersion of two-dimensional MoSe2 nanosheets in the SNG framework. In the SEM of SnSe@SNG, it can be clearly observed that SnSe nanosheets can be uniformly loaded on the surface of the SNG substrate ( Figure 5 ).
[0032] Example 4 The preparation method of the MoSe2-SnSe@SNG composite material in this embodiment includes the following steps: 1. First, 60 mg of graphene oxide was dispersed in 40 mL of a distilled water / ethanol mixed solvent (the volume ratio of water to ethanol was 3:1) to obtain a graphene suspension; then 180 mg of sodium molybdate tetrahydrate, 180 mg of sodium stannate trihydrate, 180 mg of thiourea and 540 mg of dicyandiamide were added to the graphene suspension, and stirred at room temperature for 1 hour. After stirring evenly, suspension A was obtained; suspension A was transferred into an autoclave for hydrothermal reaction at a temperature of 190°C for 18 hours; after sufficient reaction, the reaction product was cooled, centrifuged, washed and freeze-dried to obtain a precursor material; 2. The above-mentioned polymer precursor product and selenium powder were placed in a reducing atmosphere (Ar and H2 volume ratio of 95% / 5%) with a gas flow rate of 70 SCCM, and the temperature was increased to 600 °C at 3 °C / min and maintained for 2 hours to obtain a MoSe2-SnSe@SNG composite material.
[0033] Comparative Example 4 The steps are basically the same as those in the above-mentioned embodiment 4, except that in step 1, no sodium molybdate tetrahydrate or sodium stannate trihydrate is added, and the SnSe@SNG or MoSe2@SNG composite material can be obtained.
[0034] In order to demonstrate the beneficial effects of the present invention, the inventors sampled the composite materials of Examples 1 to 4 above, prepared them into working electrodes respectively, and then assembled them into lithium-ion batteries and lithium-ion hybrid capacitors respectively, and tested the electrochemical properties of the batteries and hybrid capacitors. The specific test results are as follows: (1) Preparation of working electrode The powdered composite material prepared in the above embodiment was mixed with acetylene black and polyvinylidene fluoride in a mass ratio of 7:2:1; then an appropriate amount of N-methylpyrrolidone was added to stir the mixture evenly; the mixed slurry was evenly coated on a copper foil and placed in a vacuum drying oven at 80 °C for drying; finally, it was punched into a disc with a diameter of 12 mm and weighed. According to the feed ratio, the mass of the active material in the electrode was 1.6 ± 0.1 mg cm -2 .
[0035] (2) Lithium-ion battery assembly The electrode prepared in the above step (1) was used as the working electrode, pure metallic lithium was used as the counter electrode and the reference electrode, the polypropylene porous membrane Celgard 2400 was used as the diaphragm, and the electrolyte was 1 mol / L LiPF6 / ethylene carbonate (EC)-dimethyl carbonate (DMC)-ethyl methyl carbonate (EMC), wherein the volume ratio of EC, DMC, and EMC was 1:1:1.
[0036] (3) Lithium-ion hybrid capacitor assembly The electrode prepared in the above step (1) is used as the negative electrode, activated carbon (AC) is used as the positive electrode, Celgard 2400 is used as the separator, and the electrolyte is 1 mol / L LiPF6 / EC-DMC-EMC. The mass ratio of the negative electrode to the positive electrode is set to 3:1 to assemble a MoSe2-SnSe@SNG||AC lithium-ion hybrid capacitor. Before assembling the lithium-ion hybrid capacitor, the electrode loaded with MoSe2-SnSe@SNG is tightly attached to the Li sheet, and then placed in the electrolyte containing LiPF6 for 2 hours for activation.
[0037] The entire assembly process is completed in a glove box filled with Ar atmosphere and is finally sealed with a sealing machine.
[0038] (4) Electrochemical performance test The electrochemical performance test of lithium-ion batteries and lithium-ion hybrid capacitors was performed by assembling CR2025 button batteries as test devices. The specific capacity, cycle stability and rate performance were tested by Wuhan Blue Electric CT2001A battery tester. The test results are shown in Figure 6-Figure 8 .
[0039] Figure 6 The lithium storage cycle performance of MoSe2-SnSe@SNG, MoSe2@SNG and SnSe@SNG prepared in Example 3 at different current densities of 0.2 A / g is shown in a comparative manner. Figure 6It can be seen that the corresponding charge specific capacities of the MoSe2-SnSe@SNG, MoSe2@SNG and SnSe@SNG composite materials prepared in Example 3 after 100 cycles are 780, 594, and 464 mAh / g, respectively, and the capacity retention rates are 85%, 69%, and 57%, respectively. This result shows that the electrical performance of MoSe2-SnSe@SNG is optimal, and it also proves that this synthesis method is effective. The data difference range of the cycle performance of Examples 1 to 4 is 1%-3%, among which the cycle performance of the MoSe2-SnSe@SNG composite material of Example 3 is the best. In addition, the cycle performance of the MoSe2-SnSe@SNG composite materials in Examples 1 to 4 is better than that of the MoSe2@SNG and SnSe@SNG composite materials at the same current density.
[0040] Figure 7 This is the charge and discharge curve of the MoSe2-SnSe@SNG||AC lithium ion hybrid capacitor assembled in Example 3 at a current density of 0.05 A / g, with a voltage range of 0.01~4.0 V. It can be seen that the charge and discharge curve of the lithium ion hybrid capacitor is not an ideal straight line shape, which indicates that the hybrid ion capacitor is caused by the "coupling effect" effect between two different forms of energy storage (battery and capacitor).
[0041] Figure 8 The rate performance diagram of the MoSe2-SnSe@SNG||AC lithium ion hybrid capacitor assembled in Example 3. The specific capacities of the lithium ion capacitors are 92 mAh / g, 83 mAh / g, 76 mAh / g, 66 mAh / g, 59 mAh / g, 50 mAh / g and 44 mAh / g respectively at current densities of 0.1 A / g, 0.2 A / g, 0.5 A / g, 1 A / g, 2 A / g, 4 A / g and 5 A / g. When the current density returns to 0.1 A / g, the specific capacity can be restored to 82 mAh / g. The data difference range of the rate performance of Examples 1 to 4 is 1%-4%, among which the rate performance of MoSe2-SnSe@SNG||AC in Example 3 is the best. It can be seen from the above scheme that the composite material of the present invention has the characteristics of good conductivity, controllable composition morphology structure and hierarchical composite structure, achieving a structure-activity relationship in which the structure determines the properties and the properties determine the performance. When the MoSe2-SnSe@SNG composite material provided by the present invention is used as a negative electrode material of a lithium ion battery or a capacitor, the capacity and cycle stability can be significantly improved.
[0042] It can be seen from the above scheme that the method of the present invention is simple and low-cost. The prepared molybdenum / tin selenide MoSe2-SnSe nanoparticles are loaded on sulfur-nitrogen co-doped graphene to form a three-dimensional hierarchical composite structure, which can effectively improve the conductivity of the electrode material and alleviate the volume expansion effect of the electrode material during the charging and discharging process, and can achieve the purpose of improving the electrochemical performance of lithium-ion batteries and lithium-ion capacitors.
[0043] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a molybdenum / tin selenide / sulfur-nitrogen co-doped graphene composite material, characterized in that: The process includes the following: Sodium molybdate tetrahydrate, sodium stannate trihydrate, thiourea and dicyandiamide are mixed with graphene oxide dispersion to obtain suspension A; wherein the mass ratio of sodium molybdate tetrahydrate, sodium stannate trihydrate, thiourea and dicyandiamide is 1:(0.8-2):(0.8-1.8):(1-3), and the mass ratio of sodium molybdate tetrahydrate to graphene oxide is (1.5-3):1; The suspension A is subjected to a hydrothermal reaction at 160-190° C. After the reaction is completed, the product is cooled, centrifuged, washed, and freeze-dried to obtain a precursor material; The precursor material is placed in a reducing atmosphere and calcined at 500-600° C. After the calcination, the molybdenum / tin selenide / sulfur-nitrogen co-doped graphene composite material is obtained.
2. The method for preparing a molybdenum / tin selenide / sulfur-nitrogen co-doped graphene composite material according to claim 1, characterized in that: The dispersant of the graphene oxide dispersion is a mixed solvent of water and ethanol, wherein the mixed solvent of water and ethanol is obtained by mixing water and ethanol in a volume ratio of (1-3):1; In the graphene oxide dispersion, the solid-liquid ratio of graphene oxide to dispersant is (40-60):40, and the unit is mg / mL.
3. The method for preparing a molybdenum / tin selenide / sulfur-nitrogen co-doped graphene composite material according to claim 1, characterized in that: The suspension A is subjected to hydrothermal reaction at 160-190°C for 18-22 hours.
4. The method for preparing a molybdenum / tin selenide / sulfur-nitrogen co-doped graphene composite material according to claim 1, characterized in that: After the hydrothermal reaction of suspension A is completed, the product is cooled to room temperature, and then centrifuged, washed, and freeze-dried.
5. The method for preparing a molybdenum / tin selenide / sulfur-nitrogen co-doped graphene composite material according to claim 1, characterized in that: The reducing atmosphere during the calcination of the precursor material is a mixed gas of hydrogen and argon.
6. The method for preparing a molybdenum / tin selenide / sulfur-nitrogen co-doped graphene composite material according to claim 1, characterized in that: In the mixed gas of hydrogen and argon, the volume fraction of hydrogen is 5%~10%; when the precursor material is calcined, the flow rate of the mixed gas of hydrogen and argon is 30~70 SCCM.
7. The method for preparing a molybdenum / tin selenide / sulfur-nitrogen co-doped graphene composite material according to claim 1, characterized in that: When the precursor material is calcined, the heating rate is 3 to 5°C / min and the calcination time is 2 to 3 hours.
8. A molybdenum / tin selenide / sulfur-nitrogen co-doped graphene composite material prepared by the preparation method according to any one of claims 1 to 7.
9. A lithium ion energy storage device, characterized in that: It comprises a positive electrode and a negative electrode, wherein the material of the negative electrode is the molybdenum / tin selenide / sulfur-nitrogen co-doped graphene composite material as claimed in claim 8.
10. A lithium ion energy storage device according to claim 9, characterized in that: The energy storage device is a lithium ion battery or a lithium ion hybrid capacitor.
Citation Information
Patent Citations
Preparation method and application of copper-containing catalyst for alkyne hydrochlorination reaction
CN113680355A
Molybdenum diselenide modified nitrogen-doped graphene composite material and preparation method thereof, and nitrogen-doped graphene-based lithium-sulfur battery positive electrode material
CN114512650A
Zinc selenide / polypyrrole composite material, preparation method and application thereof
CN118610417A
Preparation method of fermented coffee comprising mud
KR1020230112573A
Perovskite composite structure
US20180240607A1